Computer networking first-step - Odom, Wendell (Cisco, 2004)
Networking Basics (What Is a Network?; A Network’s Reason for Existence; Building a Network); Running the Local Department of (Network) Transportation; (How to Build a Local (Network) Roadway); Rules of the Road: How to Use the Local (Network) Roadway;... ); Shipping and Logistics: Commerce Using the (Network) Roadways (Shipping Goods over a (Network) Roadway; Choosing Shipping Options When Transporting the Goods over the (Network) Roadway;...); Navigating the Roadways to Find the Right Street Address (Delivering the Goods to the Right Street (IP) Address; Knowing Where to Turn at Each Intersection (Router);... ); Building an Interstate (Inter-LAN) Highway System.